2020
DOI: 10.3390/sym12091416
|View full text |Cite
|
Sign up to set email alerts
|

New Identities Dealing with Gauss Sums

Abstract: In this article, we used the elementary methods and the properties of the classical Gauss sums to study the problem of calculating some Gauss sums. In particular, we obtain some interesting calculating formulas for the Gauss sums corresponding to the eight-order and twelve-order characters modulo p, where p be an odd prime with p=8k+1 or p=12k+1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Tere are a number of studies with regard to the Gauss sums and their recursion properties, which can be found in [6][7][8][9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Tere are a number of studies with regard to the Gauss sums and their recursion properties, which can be found in [6][7][8][9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Many number theory problems are closely related to it. Some works can be found in references [1][2][3][4][5][6][7][8][9][10][11][12][13], which will not be listed here. For example, if p is a prime with p = 4k + 1, then p can be expressed as the sum of two squares of positive integers.…”
Section: Introductionmentioning
confidence: 99%